Development and effectiveness of solution-focused group work on self efficacy, goal orientation behavior and motivation for achievement amongst Malaysian adolescents - R. Shunmugam, Ratnadevi (2018)
Adolescents are viewed as vulnerable to peer pressure, egocentrism, risk taking, impulsivity, lack of self-control and posed irrationality and immaturity. However, many researches dispute this view as merely adult stereotypes of adolescents which persist without strong behavioral evidence. Adolescents have all the abilities and resources to flourish, grow and live a satisfying life. Past researches revealed that variables like self efficacy, goal orientation behavior and achievement motivation are key elements to produce successful adolescents. The integration of these variables enables adolescents to affirm their capability in accomplishing given tasks, assures their ability to construct goals of their own and eventually gain constant motivation to achieve goals. With well-planned interventions, adolescents can be guided to utilize their strengths to lead a successful adolescence hood. One such intervention is Solution-focused Group Work (SFGW) approach which is proven to be effective in resolving adolescents’ life struggles. This approach ought to facilitate changes in clients, in the way chosen by them. The primary purpose of this study is to develop SFGW intervention program based on Solution- Focused tenets. The study aimed to determine the effectiveness of SFGW in increasing self-efficacy, goal orientation behavior, and achievement motivation of Malaysian adolescents. This is a true experimental with pre-test and post-test design using Solution-focused module and administration of questionnaires for data collection. Descriptive analysis was used to determine the demographic characteristics and validation and reliability of SFGW intervention program. Pretest was administered to 259 samples from two secondary schools in Selangor and 66 samples were selected based on their scores in pretest. After the administration of pre-test, a total of 66 samples who met the inclusion requirement were assigned randomly to experimental (n = 32) and control (n = 34) groups using pairedmatched design. The samples in experimental group were given treatment using the SFGW intervention program for seven weeks. After the completion of the treatment, posttest and follow-up test were carried out and data was collected for dependent variables. The collected data was analyzed using descriptive statistics, paired-sample t-test, independent samples t-test, one-way repeated measure ANOVA and MANOVA. The result yielded that SFGW has good validity and high reliability with alpha Cronbach of .87 and .94 respectively. This suggests that the intervention program has consistency and reliable to be used in school setting. Paired-sample t-test measures the samples in the experimental group twice using the same questionnaire at pretest and posttest. The result discloses that the SFGW treatment increases samples self-efficacy, goal orientation behavior and achievement motivation. The analysis also concludes that SFGW is the factor in increasing self-efficacy, goal orientation behavior and achievement motivation of Malaysian adolescents. The results add value to comprehension of postmodern intervention which is suitable to be implemented in school setting as the limitation of time and number of participants in such setting. This study provides an insight on empirical finding about the suitability of Solution-focused approach in school setting. This enables counselors to refresh their theoretical knowledge and also provides alternative intervention. The study too offers new knowledge to counselors on the importance of self efficacy, goal orientation behavior and achievement motivation variables in empowering adolescents. Future researches are anticipated to explore issue of interventions especially postmodern intervention like SFGW in various settings in Malaysia.